Compensation and Incentives: Practice vs. Theory - BAKER, GEORGE P.; JENSEN, MICHAEL C.; MURPHY, KEVIN J. (Journal of Finance, 1988)
ABSTRACT A thorough understanding of internal incentive structures is critical to developing a viable theory of the firm, since these incentives determine to a large extent how individuals inside an organization behave. Many common features of organizational incentive systems are not easily explained by traditional economic theory—including egalitarian pay systems in which compensation is largely independent of performance, the overwhelming use of promotion‐based incentive systems, the absence of up‐front fees for jobs and effective bonding contracts, and the general reluctance of employers to fire, penalize, or give poor performance evaluations to employees. Typical explanations for these practices offered by behaviorists and practitioners are distinctly uneconomic—focusing on notions such as fairness, equity, morale, trust, social responsibility, and culture. The challenge to economists is to provide viable economic explanations for these practices or to integrate these alternative notions into the traditional economic model.